A Model for Implementing Accounting Information Systems in Small and Medium Sized Enterprises (Malaysian Management Journal, 2005)
Much have been researched about the issues of accounting and information systems (IS) in small and medium sized enterprises (SMEs), including their link to performance. However, past studies have struggled to show a direct impact of either accounting or IS on performance. Based on a comprehensive review of accounting and IS literature, this paper offers an alternative model to viewing the fit between accounting information systems (AIS) requirements and IS processing capacity, and assessing the link with the performance of SMEs. Using information processing theory as a theoretical foundation, the model offers new insights into the potential factors that influence AIS requirements, types of IT sophistication and its link to IS processing capacity, the fit between AIS requirements and IS processing capacity, and the potential impact of aligning AIS requirements and IS processing capacity on overall firm performance.